HUBUNGAN KEMAMPUAN KERJA DAN MOTIVASI KERJA DENGAN KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TEMANGGUNG - Ayu Maharsi Cendanawangi; Mochammad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The main of issues that often happen in public organizations are the level ofemployee performance, there are optimal and low. Employee performance refers totwo meanings, that are result and behavior. Performance as a result is the result ofproduced on a particular job function or activities over a period of time, whereasperformance as behavior is actions or behaviors that are relevant to the goals of theorganization.There are two factors that affect employee performance, they are motivationand ability. Each employee has a different performance. There are employees whoalways want their work done on time so that the employee is always the spirit incarrying out his work. But there are also employees who are not too eager incarrying out their work and often late to come to the office. The purpose of this studyis to determine the relationship of work ability with employee performance, knowingthe relationship of work motivation with employee performance, and work abilityand work motivation with employee performance in Dinas Kependudukan danPencatatan Sipil Kabupaten Temanggung. The results showed that there is arelationship with the performance of employee performance. This relationship isparticularly evident with the ability to manage tasks, and social and culturalmanageability. The insignificant relationship occurs between the motivation ofachievement and the motivation of affiliation with employee performance, while themotivation to power shows a significant relationship with employee performance. Ingeneral it can be said that there is no significant relationship between workmotivation and performance, the relationship is only seen between the motivationwill power with performance.To improve the performance of employee suggestions provided in this case isnecessary to improve the ability of work, especially the ability to manage tasks, andability to manage social and cultural and improve work motivation, especially